CADD-23. PD-L1 CHECKPOINT BLOCKADE USING A SINGLE-CHAIN VARIABLE FRAGMENT TARGETING PD-L1 DELIVERED BY RETROVIRAL REPLICATING VECTOR (TOCA 521) ENHANCES ANTI-TUMOR EFFECT IN CANCER MODELS. (5th November 2018) - Lin, Amy; Yagiz, Kader; Hofacre, Andrew; Munday, Anthony; Espinoza, Fernando Lopez; Mendoza, Daniel; Burrascano, Cynthia; Gruber, Harry; Mitchell, Leah; Jolly, Douglas
Abstract: Conventional interventions for treating glioblastoma (GBM) patients has had limited success, with a median overall survival of 15–17 months. Recently, immune checkpoint inhibitors (CPIs) showed long-term response rates from 20–30% in some tumors, but no consistent clinical benefit with these agents has been demonstrated so far in GBM patients. We propose and provide preliminary evidence for a strategy using retroviral replicating vectors (RRV) to deliver CPI agents selectively to cancer cells that may circumvent such issues. An RRV encoding a single-chain variable fragment targeting PD-L1 (RRV-scFv-PDL1, Toca 521) binds to both mouse and human PD-L1 by competitive ELISA and competes for target occupancy with a commercially available monoclonal antibody against cell surface PD-L1. A dose-dependent bystander effect is observed with scFv PD-L1 protein expressed from RRV-scFv-PDL1 infected tumor cells showing saturated receptor binding to the cell surface PD-L1 of bystander cells when co-cultured with as low as 10% scFv PD-L1 expressing cells. In addition, the immune functional activity of scFv PD-L1 to reverse PD-1/PD-L1 mediated immune suppression was observed in a co-culture system in vitro and further supported by in vivo mouse models. Such models included a syngeneic orthotopic glioma showing that tumors infected with RRV-scFv-PDL1 conferred robust and durable immune-mediated antitumor activity superior to systemically administered anti-PD-1/anti-PD-L1 monoclonal antibodies. These results support the concept that RRV-scFv-PDL1 CPI strategy may provide an improved safety and efficacy profile compared to systemic monoclonal antibodies. The superior anti-tumor activity of RRV-scFv-PDL1 may be due to consistent high levels of scFv PD-L1 within the tumor microenvironment. This localized delivery approach with less concern for autoimmune adverse events may be therapeutically beneficial as an immuno-oncology agent either alone or in combination.